二十一世纪河北粮食问题展望与思考 = Hebei's food security issues in the 21st century : outlook and implications - 吴兵冲 Wu, Bing Chong (2011)
As a strategically essential material for survey, food has always been important to China's economic development and social stability. With relatively small arable land to grow food for huge population, consensus among Chinese policy makers is to stress the importance of food production. China has vast land and various natural conditions. Based on its unique natural condition, each province needs to figure out how to best solve its food security issues The goal of this paper is to make some policy recommendations to solve Hebei's food security issues in the 21st century. This paper first reviewed past food production and demand situations in Hebei. After providing future food demand and supply estimates, this paper discussed some policy recommendations on solving Hebei's food security problems. It seeks to achieve efficient resource allocation, stead increase in food production and economic efficiency. It is concluded that the goal of food security in Hebei can be reached so long as following recommendations are implemented: insisting market orientation, increasing economic efficiency, enhancing infrastructure construction, applying high-tech in agricultural production, and improving market distribution.